2020
DOI: 10.9734/jsrr/2020/v26i930305
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bacterial Leaf Spot of Bottle Gourd and Pumpkin in Subtropical Zone of Himachal Pradesh

Abstract: To assess the prevalence and severity of bacterial leaf spot on bottle gourd and pumpkin, a survey was conducted in Hamirpur, Una and Bilaspur districts of sub tropical zone of Himachal Pradesh, India during the years 2018 and 2019. Data were recorded in terms of disease severity and fruit rot incidence. The associated pathogen from bottle gourd and pumpkin was isolated on nutrient sodium chloride agar medium and identified on the basis of morphological, biochemical and pathogenicity tests on bottle gourd and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The results were in accordance with findings of many workers who have reported that a bacterial concentration of 10 5 to 10 8 cfu/ml is able to incite pathogenic reaction in different cucurbit hosts. (Pruvost et al, 2009;Lamichhane et al, 2010;Jarial et al, 2011;Babadoost and Ravanlou, 2012;Dutta et al, 2013;Trueman et al, 2014). During present studies, syringe inoculation method proved best for the initiation and development of the disease, followed by pin prick and leaf margin methods of inoculation in both bottle gourd and pumpkin isolates of the pathogen.…”
Section: Effect Of Different Methods Of Inoculation On Disease Development In Bottle Gourd and Pumpkinmentioning
confidence: 56%
See 2 more Smart Citations
“…The results were in accordance with findings of many workers who have reported that a bacterial concentration of 10 5 to 10 8 cfu/ml is able to incite pathogenic reaction in different cucurbit hosts. (Pruvost et al, 2009;Lamichhane et al, 2010;Jarial et al, 2011;Babadoost and Ravanlou, 2012;Dutta et al, 2013;Trueman et al, 2014). During present studies, syringe inoculation method proved best for the initiation and development of the disease, followed by pin prick and leaf margin methods of inoculation in both bottle gourd and pumpkin isolates of the pathogen.…”
Section: Effect Of Different Methods Of Inoculation On Disease Development In Bottle Gourd and Pumpkinmentioning
confidence: 56%
“…Significant losses have been reported in different cucurbits due to this disease. In bottle gourd, significant (20-70 %) losses have been reported by Larazev ( 2009), Jarial et al, (2011) and Basit et al, (2014) while in pumpkin, Salamanca (2014) reported up to 90 per cent losses.…”
Section: Issn: 2319-7706 Volume 9 Number 6 (2020)mentioning
confidence: 87%
See 1 more Smart Citation
“…X. campestris pv. cucurbitae) causing bacterial spot is emerging as an important pathogen leading to huge crop losses especially to bottle gourd, pumpkin and squashes (Jarial et al, 2011;Babadoost, 2012;Babadoost, 2017). This disease was first reported as bacterial leaf spot on Hubbard squash in New York in 1925 by Bryan (Bryan, 1930).…”
mentioning
confidence: 99%
“…and on bottle gourd (Jarial et al, 2011;Jarial et al, 2015;Sharma, 2016) from different countries of world.The disease has been reported to cause significant losses in different cucurbits. According to Larazev (2009), yield losses reach more than 20% in susceptible cultivars however, the disease severity reaches up to 50-60% at fruit storage in various cucurbits.…”
mentioning
confidence: 99%